An Iconographical Study of the Sema Tawy Motif in Ancient Egypt, and its use in Southwest Asia from ca. 3000 BCE – 400 CE - Meyer, Marlene Anchen (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.